Study of Kacang Goat Breeding Program Using Qualitative Analysis Methods - Apri Irianto; Wiyan Afriyanto Pamungkas; N. Nurcholis; Syetiel Maya Salamony; Desmina K. Hutabarat (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2023)
Merauke has several kinds of livestock that have the potential to be well-developed to meet the needs of animal protein. This study aims to find out how the Kacang goat breeding program in Tanah Miring District by looking at several qualitative parameters on breeders including; education level, livelihood, rearing system, livestock origin, and ownership status. Data were collected using questionnaires and analyzed using descriptive analysis assisted by MS Excel for data tabulation. The results showed that the level of formal education at the elementary level dominated the characteristics of Kacang goat breeders in Tanah Miring District with the main livelihood as a farmer. The intensive maintenance system predominates in Tanah Miring District. As many as 80% of respondents answered that Kacang goats were livestock purchased from outside the Tanah Miring District area and the rest were those born in the area.